2016
DOI: 10.1098/rspb.2016.0392
|View full text |Cite
|
Sign up to set email alerts
|

Historical baselines and the future of shell calcification for a foundation species in a changing ocean

Abstract: Seawater pH and the availability of carbonate ions are decreasing due to anthropogenic carbon dioxide emissions, posing challenges for calcifying marine species. Marine mussels are of particular concern given their role as foundation species worldwide. Here, we document shell growth and calcification patterns in Mytilus californianus, the California mussel, over millennial and decadal scales. By comparing shell thickness across the largest modern shells, the largest mussels collected in the 1960s-1970s and she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 64 publications
5
30
0
Order By: Relevance
“…Excavation of Native American middens from the Makah Tribe (McMillan, ), who used Tatoosh Island as a summer camp prior to the 1800s and historically had a large settlement at Sand Point, provided ‘midden’ valves from Tatoosh Island through the Makah Cultural and Resource Center, while Sand Point midden material was provided by the Olympic National Park. These shells were radiocarbon dated using shell material from their most recent year of growth, with Tatoosh Island midden shells dated to 1000–1340 years BP in 2010 (Pfister et al., ) and Sand Point midden shells dated to 2150–2440 years BP in 2015 (Pfister et al., ). Valves were cross‐sectioned along their axis of maximum growth using a slow‐speed saw with a diamond blade to make a 3 mm‐thick cross‐section.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Excavation of Native American middens from the Makah Tribe (McMillan, ), who used Tatoosh Island as a summer camp prior to the 1800s and historically had a large settlement at Sand Point, provided ‘midden’ valves from Tatoosh Island through the Makah Cultural and Resource Center, while Sand Point midden material was provided by the Olympic National Park. These shells were radiocarbon dated using shell material from their most recent year of growth, with Tatoosh Island midden shells dated to 1000–1340 years BP in 2010 (Pfister et al., ) and Sand Point midden shells dated to 2150–2440 years BP in 2015 (Pfister et al., ). Valves were cross‐sectioned along their axis of maximum growth using a slow‐speed saw with a diamond blade to make a 3 mm‐thick cross‐section.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that the thickness of annual growth bands within the inner prismatic layer of M. californianus is reduced by approximately half when comparing modern day specimens to shells dated to 1000–1340 years BP at Tatoosh Island, WA (Pfister et al., ), suggesting that modern shells may be experiencing stress associated with biomineralization through time. Here, we present a study of shell structure from the California mussel, M. californianus , spanning decadal and centennial scales to determine the long‐term effects of changes in ocean carbon chemistry on shell mineralogy in a natural system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced pH can affect metabolism and energy budgets in marine organisms, particularly in organisms that produce calcium carbonate for shells or skeletons (Kroeker et al, 2010;Harvey et al, 2013Harvey et al, , 2016. For example, calcification rates in Mytilus californianus mussels in Washington State, USA, have decreased significantly, probably due to declining pH (Pfister et al, 2016). Mussel beds are the dominant space occupier of many temperate rocky shore coastlines around the planet.…”
Section: Box 3 7 5 Contmentioning
confidence: 99%